New Surgical Options in Glaucoma - Heckler, Lisa V; Dorey, Michael W; Damji, Karim F (Canadian Journal of Optometry, 2015)
The treatment of glaucoma is undergoing constant change. In the last decade, there has been a surge of novel surgical options that aim to lower intraocular pressure while providing improved safety profiles compared to traditional incisional glaucoma surgery. This article summarizes four such options— trabectome, iStent, canaloplasty and endocyclophotocoagulation— including descriptions of the procedures and evidence behind them.